(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2025)
The aim of this study is to reflect on the artistic and philosophical approaches belonging to the narrative, interactive, and playable world of the video game Scorn, which have been drawn from the work of H.R. Giger, creator of the xenomorph design for Alien: The Alien and proponent of biomechanical art. Through an interdisciplinary approach combining posthumanist theory, visual studies, and video game design analysis, the influence of Giger on the artistic direction of this digital work is explored, focusing on its symbolic elements (organic-mechanical architectures, hybrid creatures, and bodily imagery) and its biopunk, decaying atmosphere. The study examines how Gigerian aesthetics — which fuse organism and machine — are reinterpreted in Scorn to articulate a critical discourse on the posthuman condition. It is also concluded that Giger’s work has been transferred to Scorn through a posthumanist narrative characterized by existential absurdism and scientific determinism, packaged in the Swiss artist’s biomechanical and sexualized art.